Bridging the digital gap: Impact of digital marketing training on women-led MSMEs in Klaten - Husna, Faizah Khotimatul; Tamtama, Noviandry Nur; Syahputri, Rezyana Budi; Al Hakim, Humairoh (Nur Science Institute, 2025)
Digital inequality continues to limit women entrepreneurs in rural and semi-urban areas from fully participating in the digital economy. Strengthening digital marketing literacy is essential to improve their business competitiveness and market access. This study aimed to evaluate the effectiveness of a digital marketing training in improving the digital marketing literacy of women-led micro, small, and medium enterprises (MSMEs) in Klaten, Central Java. A one-group pretest-posttest pre-experimental design was employed with 35 participants selected through purposive sampling. The training intervention was delivered in a one-day session and measured through two key indicators: understanding of digital marketing concepts and responsible use of social media. Each indicator consisted of Likert-scale questions administered before and after the training. The results showed a clear improvement in participants’ knowledge and skills across both indicators, with higher mean scores recorded after the training. These findings suggest that even short-format, context-driven digital training can enhance both conceptual and ethical digital marketing literacy among women entrepreneurs. The study provides insights into the feasibility of replicating such interventions in other community-based empowerment programs for female MSMEs.